Planejamento da provisão para contingência tributária federal - Belchior, Flávio Silva (2011)
With the edition of Law nº 11.638/07, amending provisions of Law n°. 6404/76, officially began the process convergence of Brazilian accounting standards with international accounting standards (International Financial Reporting Standards - IFRS) issued by the International Accounting Standards Board (IASB). Earlier, the Brazilian Institute of Independent Auditors (IBRACON) had already published the Accounting Standard and Procedure nº 22 (October 2005), since in order to harmonize accounting norms on Liabilities, Contingent Liabilities and Contingent Active at international (in this case, the International Accounting Standard 37). The present work aims to draw a parallel between the rules currently in place with the Brazilian reality as to time to conduct judicial proceedings in order to detect which time (time) most appropriate for the eventual recognition a provision, contingent liability for the federal tax. They were used part of the result of research conducted by the Institute for Applied Economic Research IPEA, recently advertised through Announcements No. 83 and 87 (Unit Cost of Execution Process Audit in the Federal Court), and its Research Report, which uses ABC method to describe and measure the activities of the Federal Court. This research is descriptive and their approach, analysis and interpretation of data occurs quantitatively and qualitatively. The population is 184 and the federal courts is the sample of 1,510 court cases completed in 2009